2021
DOI: 10.1109/access.2021.3098979
|View full text |Cite
|
Sign up to set email alerts
|

When the Timeline Meets the Pipeline: A Survey on Automated Cyberbullying Detection

Abstract: Web 2.0 helped user-generated platforms to spread widely. Unfortunately, it also allowed for cyberbullying to spread. Cyberbullying has negative effects that could lead to cases of depression and low self-esteem. It has become crucial to develop tools for automated cyberbullying detection. The research on developing these tools has been growing over the last decade, especially with the recent advances in machine learning and natural language processing. Given the large body of work on this topic, it is vital t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 112 publications
(309 reference statements)
1
32
0
Order By: Relevance
“…This experiment not only underlines the strong focus on lexical cues 13 from linear classifiers, but also that transformer models are not immune to lexical variation-even when candidates are sampled from their own language model. This provides further evidence in line with research from Elsafoury et al (2021a), and Elsafoury et al (2021b) (see Section 5). Semantic Consistency of Samples Here, we compared X pos with X pos as a reference.…”
Section: The Effect Of Lexical Variationsupporting
confidence: 91%
See 2 more Smart Citations
“…This experiment not only underlines the strong focus on lexical cues 13 from linear classifiers, but also that transformer models are not immune to lexical variation-even when candidates are sampled from their own language model. This provides further evidence in line with research from Elsafoury et al (2021a), and Elsafoury et al (2021b) (see Section 5). Semantic Consistency of Samples Here, we compared X pos with X pos as a reference.…”
Section: The Effect Of Lexical Variationsupporting
confidence: 91%
“…We follow recent state-of-the-art results (Elsafoury et al, 2021a) for our main classification model, and finetune all BERT-based models for 10 epochs with a batch size of 32 and a learning rate of 2e−5, as suggested by Devlin et al (2019). Accordingly, we set the maximum sequence length to 128, and insert a single linear layer after the pooled output.…”
Section: Classifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Tripathy et al [ 37 ] used fine-tuned ALBERT model for cyberbullying detection by using ALBERT-large, a larger pretraining corpus over the BERT-Base that Mozafari et al [ 34 ] implemented. Elsafoury et al [ 13 ] conducted experiments using BERT for cyberbullying detection in comparison to the DL models used in the literature. The results of their experiments found that using BERT improved the detection, and they found that there is lack of research on the use of BERT for cyberbullying detection.…”
Section: Cyberbullying Detection Approachesmentioning
confidence: 99%
“…Rosa et al [ 12 ] conducted an analysis by performing quantitative systematic review of 22 studies on automatic cyberbullying detection. Elsafoury et al [ 13 ] also presented a systematic review by reviewing the literature on automated cyberbullying detection and identifying the limitations in the available works. They also conducted experiments on the limitations they identified on the available automated cyberbullying detection and investigated their impact on the performance of cyberbullying detection.…”
Section: Introductionmentioning
confidence: 99%